On maximum-entropy and related principles in statistical equilibrium - C. G. Chakrabarti; V. Mukhopadhyay (International Journal of Mathematics and Mathematical Sciences)
The paper aims to study the importance and equivalence of the principles of maximum-entropy, and sufficient and stable inferences in the statistical characterization of the thermal equilibrium of a closed system.